Pengaruh Penggunaan Berbagai Jenis Media Tanam dan Jenis Sumbu Terhadap Pertumbuhan dan Hasil Tanaman Kailan (Brassica Oleraceae Var. Alboglabra) pada Hidroponik Sistem Wick - Rifani Tiara Rahmanda Albadri; Muharam Muharam; Yayu Sri Rahayu (Peneliti.net, 2022)
Kailan is one type of vegetable that has high economic value. One way to produce nutritious food products in the form of vegetables is by planting using a hydroponic system. The hydroponic system has various systems, one of which is the wick system Wick. This experiment was carried out at Screen House Village. Selang Tengah RT04/RW02, Ward. Wanasari, Districts. Cibitung, Regency. Bekasi, West Java. It was carried out from March to May 2022. The research method used was an experimental method using a factorial Randomized Block Design (RBD), which consisted of 9 treatments repeated 3 times. The first factor is the planting medium consisting of 3 levels, namely m1 (rockwool), m2 (sand of Malang) and m3 (fern). the second factor consisted of 3 levels, namely s1 (flanel), s2 (stove wick) and s3 (wool). The experimental data obtained were carried out by the 5% level F test. There was an interaction effect between the planting medium and the type of axis on the number of kailan leaves at the age of 14 and 42 days after planting the hydroponic wick system. The M1S3 (rockwool + flannel) planting media treatment gave the highest number of leaves of 11.47 strands, but it was not significantly different from M2S1 (sand + wool). Rockwool growing media gave the highest fresh weight of 111,29 g, while the woolen wick gave a fresh weight of 106,53 g